Audzināšana ģimenē Latvijas transformatīvajā sabiedrībā - Medne, Dace (Latvijas Universitāte, 2010)
Family Child-Rearing Practices in the Transformative Society of Latvia Abstract Keywords: child-rearing practices in the family, educational field, parental competence in child-rearing The current research has grown out of changes in the family child-rearing practices caused by the transformative situation of the Latvian society and socialphilosophical paradigm shift. The research emphasizes individual’s autonomy within the framework of a social system and focuses on parental competence in child-rearing. The empirical part of the research has 3 stages: first, a pilot research was conducted. Second, a questionnaire was distributed in order to gather data on parental competence in child-rearing in contemporary Latvia. For the second stage of the research, a biographical approach was chosen: the pedagogic situation was investigated and a portrait was created of a family promoting positive human experience. In the third stage of the research, the collected data was analized and interpreted using mix-methods, i.e. integrating the qualitative and quantitative research methods. The quantitative data was analized using the SPSS 15.0 system while in processing the qualitative data, AQAD 6 was used.
Family Child-Rearing Practices in the Transformative Society of Latvia
Elektroniskā versija nesatur pielikumus
Keywords: Pedagoģija; Izglītība, pedagoģija un sports